2019
DOI: 10.1016/j.cell.2019.04.009
|View full text |Cite
|
Sign up to set email alerts
|

A High-Throughput Platform to Identify Small-Molecule Inhibitors of CRISPR-Cas9

Abstract: Highlights d Developed high-throughput assays for SpCas9 and performed a small-molecule screen d Identified reversible and cell-permeable inhibitors that disrupt SpCas9-DNA binding d Inhibitors allow dose and temporal control of (non)-nucleasebased SpCas9 systems d Identified a pharmacophore for SpCas9 inhibition using structure-activity studies

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
159
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 148 publications
(163 citation statements)
references
References 52 publications
(51 reference statements)
0
159
0
Order By: Relevance
“…Finally, to investigate the off-target profile of the Cas9-adaptor conjugates, we used an eGFP disruption assay with matched gRNA and mismatched gRNAs targeting the eGFP gene, in U2OS.eGFP.PEST cells. 30,31 The Cas9-adaptor conjugate retained the target specificity while maintaining the on-target activity ( Figure S4).…”
Section: Resultsmentioning
confidence: 96%
“…Finally, to investigate the off-target profile of the Cas9-adaptor conjugates, we used an eGFP disruption assay with matched gRNA and mismatched gRNAs targeting the eGFP gene, in U2OS.eGFP.PEST cells. 30,31 The Cas9-adaptor conjugate retained the target specificity while maintaining the on-target activity ( Figure S4).…”
Section: Resultsmentioning
confidence: 96%
“…Despite the elusive biological relevance of the anti-CRISPR activity of G8P, we nevertheless demonstrated that the genome-editing activity of SpyCas9 in human cells can be modulated by G8PPD. To the best of our knowledge, our discovery represents the first peptides known to exhibit Cas9-inhibiting activity and expands the anti-CRISPR agent toolbox which is currently composed of anti-CRISPR proteins [21], smallmolecules [20] and synthetic oligonucleotides [59]. Compared with Acr proteins that are typically 10 to 20 kD in size, G8PPD peptides are small in size and can be chemically proposed that the specificity of SpyCas9 in human cells may be increased by partial inhibition with weak CRISPR-Cas inhibitors [20].…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, our discovery represents the first peptides known to exhibit Cas9-inhibiting activity and expands the anti-CRISPR agent toolbox which is currently composed of anti-CRISPR proteins [21], smallmolecules [20] and synthetic oligonucleotides [59]. Compared with Acr proteins that are typically 10 to 20 kD in size, G8PPD peptides are small in size and can be chemically proposed that the specificity of SpyCas9 in human cells may be increased by partial inhibition with weak CRISPR-Cas inhibitors [20]. In the current study, we found that transfection of strong CRISPR-Cas inhibitor AcrII4A inhibited SpyCas9 activity to near complete in human cells when transfected prior to ( Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It might be possible to use HDAC3 inhibitors for turning down the activity of Cas9. The first small molecular Cas9 inhibitors have been uncovered recently which can be used for inactivating Cas9 activity34 . Although those inhibitors are with high potency, they might be only effective for SpCas9.…”
mentioning
confidence: 99%